Multi-Country Experience in Delivering a Joint Course on Software Engineering – Numerical Results - Budimac, Zoran; Putnik, Zoran; Ivanović, Mirjana; Bothe, Klaus; Zdravkova, Katerina; Jakimovski, Boro (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
A joint course, created as a result of a project under the auspices of the ‘Stability Pact of South-Eastern Europe’ and DAAD, has been conducted in several Balkan countries: in Novi Sad, Serbia, for the last six years in several different forms, in Skopje, FYR of Macedonia, for two years, for several types of students, and in Tirana, Albania, in the form of a crash, 7-day course, for the last two years. In this paper, we will put an emphasis on the assessment methods used within these courses, and compare them with the ‘original’ course that has been conducted at the Humboldt University in Berlin for almost a decade. Having a good environment for comparisons we draw some conclusions about teaching software engineering in different environments.